Mobile-assisted Autonomous English Learning in College Students’ Extra-curriculum Time: A Case Study in China - Li, Xueting (Technium Social Sciences Journal, 2021)
With the growth of science and information technology in today’s digital era, mobile-assisted learning is increasingly becoming an essential element in English learning for college students. In the context of the current construction of foreign language education in the new era, online autonomous learning is becoming a trend, especially in the anti-coronavirus stage. Moreover, how to provide adequate learning support for online autonomous learners is a research topic in the current education field. This study aims to investigate English-major students’ mobile-assisted learning in Chinese engineering colleges in response to this research gap. This paper explores the current state of mobile-assisted autonomous English learning in extra-curricular time based on the statistical study of surveys, using questionnaires and online interviews. Results showed that English majors spent some time learning online with mobile devices, and they need help with online autonomous learning. Further, this article provides suggestions on instructing English majors’ online learning.